A new species of the genus Achalinus (Squamata: Xenodermidae) from Nanning, Guangxi, China - Yang, Dian-Cheng; Xu, Yu-Hao; Wu, Jia-Xiang; Gong, Yan-An; Huang, Ru-Yi; Xiang, Jun; Feng, Zheng-Lian; Huang, Tian-Qi; Huang, Song (Zootaxa, 2023)
We describe a new species of the genus Achalinus Peters, 1869 from Daming Mountain, Shanglin County, Nanning City, Guangxi Zhuang Autonomous Region, China, based on a single adult male specimen. It can be distinguished from all the other species in Achalinus by a combination of the following morphological characters: (1) a bright yellow collar around the neck, extending forward to the ventral of the head; (2) tail length comparatively long, TaL/Tol ratio 0.25; (3) DSR 23-23-23, moderately keeled; (4) VS 3+162; (5) SC 74, unpaired; (6) cloacal plate entire; (7) SPL 6, the fourth and fifth in contact with the eye; (8) IFL 6, the first three touching the first pair of chin shields; (9) a single loreal; (10) length of suture between internasal significantly longer than that between prefrontal, LSBI/LSBP ratio 1.34; (11) two pairs of chin shields; (12) longitudinal vertebral line absent. In addition, the uncorrected p-distances between the new species and other known congeners ranged from 6.3% to 25.4% for the cytochrome c oxidase subunit 1 (CO1). With the addition of the new species the total number of described Achalinus species is increased to 23 of which 17 are found in China.